2009
DOI: 10.5001/omj.2009.40
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Cancer Patients undergoing Chemotherapy

Abstract: This study suggests that encouraging cancer patients to complete a CT course plays an important role in the treatment outcome and the QoL in cancer patients undergoing CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
39
5
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 23 publications
10
39
5
12
Order By: Relevance
“…Similarly, Gray et al (2011) have reported that patients with lower income have lower life quality. Contrary to the present study, a study has shown that economical status has no effect on life quality (Dehkordi et al, 2009).…”
Section: Eortc Qlq C-30 Scorescontrasting
confidence: 99%
See 4 more Smart Citations
“…Similarly, Gray et al (2011) have reported that patients with lower income have lower life quality. Contrary to the present study, a study has shown that economical status has no effect on life quality (Dehkordi et al, 2009).…”
Section: Eortc Qlq C-30 Scorescontrasting
confidence: 99%
“…A study on colorectal cancer patients has shown that female patients have lower life quality (Gray et al, 2011). Another study has shown that gender has no effect on life quality (Dehkordi et al, 2009). In the present study, we found that patients who were secondary school graduate/graduate/postgraduate experienced more functional difficulties compared to patients who were literate/elementary school graduate.…”
Section: Eortc Qlq C-30 Scorescontrasting
confidence: 43%
See 3 more Smart Citations